2016
DOI: 10.1007/s00221-016-4592-x
|View full text |Cite
|
Sign up to set email alerts
|

Gait patterns in children with Developmental Coordination Disorder

Abstract: Previous research has shown that adults with Developmental Coordination Disorder (DCD) show increased variability of foot placement measures and movement of the centre of mass (CoM) while walking. The current study considered the gait patterns of young and older children with DCD. Fourteen young children with DCD (7-12 years), 15 older children with DCD (12-17 years) and 29 age- and gender-matched typically developing children took part. Children were asked to walk up and down a flat 10-m-long pathway for 1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Six articles examined gait patterns in DCD, five of these in children and one in adults (Table SV). Two studies characterized walking patterns in DCD . Wilmut et al showed that children with DCD had wider normalized steps and higher variability in double support time and stride time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles examined gait patterns in DCD, five of these in children and one in adults (Table SV). Two studies characterized walking patterns in DCD . Wilmut et al showed that children with DCD had wider normalized steps and higher variability in double support time and stride time.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies characterized walking patterns in DCD . Wilmut et al showed that children with DCD had wider normalized steps and higher variability in double support time and stride time. A similar pattern was observed for adults …”
Section: Resultsmentioning
confidence: 99%
“…According to the above mentioned concepts of variability and stability, variability indexes, usually applied on stride time data, are meant to assess changes in the peripheral realization of the gait pattern [7,8,13,14], whereas stability indexes, usually applied on trunk acceleration data, are meant to assess the stability of the trajectory of the centre of mass. Indeed, recent studies [13,15,16], analysing both healthy (from 4 years-old children to 25 years-old young adults) and pathological subjects (stroke), analysed the role of the variability in joint kinematics in determining a successful control of the stability of the centre of mass trajectory, approximated by the lower trunk [7,17,18]. Stride time and trunk acceleration data are two manifestations of the same control system in healthy and pathologic subjects [19,20].…”
Section: Table Nomenclature Herementioning
confidence: 99%
“…Children and adults with DCD have been noted to have different gait patterns from individuals without DCD, including an awkward gait and frequent stumbling or bumping into objects in their path . Evidence on the gait patterns of children with DCD suggests that they have poor head control, uncoordinated limb to limb transitions, increased step width, and increased time in double support in order to increase base of support and maintain dynamic balance .…”
Section: Introductionmentioning
confidence: 99%